Pengaruh Model Pembelajaran Contextual Teaching and Learning (CTL ) terhadap Hasil Belajar Siswa Kelas III pada Materi Butir – butir Pancasila SDN Petemon Surabaya (Sekolah Tinggi Agama Buddha Nalanda, 2023)
This research is motivated by the lack of students in applying Pancasila practice in everyday life. One way that can be used in this case is the Contextual Teaching and Learning (CTL) learning model. The purpose of this study was to determine the effect of the CTL learning model on the learning outcomes of class III students on Pancasila items at SDN Petemon Surabaya. The type of research used is quantitative using the experimental method, with the type of Pretest-Posttest Control Group Design. This study uses a population of class 3 SDN Petemon Surabaya. Class 3A has 28 students as the control class and class 3B has 28 students as the experimental class. The research instrument used pretest and posttest questions which contained 10 multiple choice questions. The data collection technique used the pretest and posttest standard values, the tests used were: normality test, homogeneity test, and hypothesis testing. The results of the data analysis produced by the experimental posttest were higher than the control. This proves that there is an influence of the CTL learning model on the learning outcomes of class III students on Pancasila items at SDN Petemon Surabaya.